Faktor-Faktor Yang Mempengaruhi Cash Holding Perusahaan Manufaktur Tahun 2017-2019 - Garry Linggo, Viriany, Henny Wirianata (Jurnal Paradigma Akuntansi, 2022)
The purpose of this research is to examine the effect of leverage, firm size, profitability, liquidity, and net working capital on cash holding of manufacturing company listed on Indonesia Stock Exchange (IDX) during period 2017-2019. The sample used is 70 companies, the sample was selected using purposive sampling method. Data processing techniques using Eviews 10. The result showed that leverage variable has insignificant negative impact on cash holding, firm size has insignificant negative impact on cash holding, profitability has insignificant positive impact on cash holding, liquidity has significant positive impact on cash holding and net working capital has insignificant negative impact on cash holding. The implication of this study is to consider liquidity and net working capital for optimalization of company’s cash holding.